Mutations of the ras gene product p21 that abolish guanine nucleotide binding. - Clanton, D J (1986)
We have constructed several point mutations affecting the GTP-binding site of p21, the ras-encoded protein. Both lysine (116K) and tyrosine (116Y) mutations of asparagine-116, which, by analogy with the crystal structure of elongation factor Tu (EF-Tu), has critical interactions with the guanine base, abolish GTP binding and transforming activities of p21. These activities are retained by proteins with a mutation at position 117 or 118. Both 116K and 116Y mutant p21s, when overproduced in Escherichia coli, are apparently devoid of GTP-binding and autokinase activities. Similarly, the mutant DNAs do not transform NIH 3T3 cells in a focus-forming assay. By cotransfection with pSV-neo, cell clones resistant to the neomycin analog G418 have been isolated. Cells transfected with 116K or 116Y mutant DNA are contact inhibited. In contrast to competent clones, the defective mutants have no detectable phosphorylated p21. The present results suggest that the basic structure of the GTP-binding site is conserved between p21 and EF-Tu and that this binding site is crucial for ras gene function.